Empoderamento e self: um estudo sobre mulheres que viajam sozinhas - Melo, Camila Santos (2021)
The relationship between consumption and self has been largely discussed in the literature. Consumption is not an isolated or merely functional act. Nowadays a new social phenomenon is gaining relevance: solo consumption. This phenomenon is a reflection of a social transition, where consuming alone gains new meanings and signifiers. Tourism, which is a consumption practice with various associated meanings, stands out in the dynamics of solo consumption. In terms of gender, women who travel alone gain relevance, not only for the growing market niche they represent, but for this act to relate to their self-expression, identity project and achievement of freedom and independence. The present study had as main objective to understand how the relationship between the act of traveling alone by women and the expression of their self happens, having as a social context the female empowerment and the development of virtual platforms of connection between solo travelers. Through the qualitative approach, twelve women who travel alone were interviewed with the support of a semi-structured interview and the results reveal that the consumption of solo travel is a booster of the process of self empowerment. Four main moments in the women's journey were identified that drive the affirmation of the empowered self: the decision process of the first solo trip; the risk mapping and the search for tools to reduce the risks; the journey and the awakening of the pains and pleasures of being alone; The return to routine: the effect of the freedom experienced and the consolidation of solo travel as a habit of consumption and lifestyle. These four moments symbolize breaking points in the life of the group of women solo travelers analyzed and going through them proved to be fundamental for the transformation and affirmation of the empowered self. Therefore, it is argued that solo travel goes beyond the material dimensions of its consumption and becomes an essential part of the lifestyle and expression of the empowered self of women.